Pelaksanaan Pemutusan Hubungan Kerja Dalam Perjanjian Kerja Waktu Tertentu Secara Sepihak Oleh Pt. Hotel Sahid Jaya International, Tbk (Studi Putusan Pengadilan Negeri Jakarta Pusat Nomor 186/Pdt.Sus/Phi/2019/Pn.Jkt.Pst.) - Muhammad Ariq; Aju Putrijanti (UNES Law Review, 2023)
The writing of this scientific work discusses unilateral termination of employment (PHK), which is a layoff carried out on workers or laborers without going through the process regulated by the employment law, therefore the government issued Law Number 13 of 2003 concerning employment. The main problem of this research is what are the legal consequences of termination of employment carried out by PT. Hotel Sahid Jaya International to a worker named Viveka Nanda, based on Law Number 13 of 2003 concerning Employment, and whether the judge's decision in the district court decision Number 186/Pdt.Sus-PHI/2019/PN.Jkt.Pst. is in accordance with applicable laws and regulations. Normative Juridical using secondary data. In terms of data processing, it is carried out qualitatively, namely a method that produces analytical descriptive information. The research results are the Central Jakarta District Court Decision Number 186/Pdt.Sus/PHI/2019/PN.Jkt.Pst. not in accordance with statutory regulations regarding employment Number 13 of 2003, the layoff dispute case that occurred between Viveka Nanda as the plaintiff and PT. Hotel Sahid Jaya International as the defendant as a result of the law is null and void. In this case, the judge's decision in district court decision Number 186/Pdt.Sus-PHI/2019/PN.Jkt.Pst. not in accordance with applicable laws and regulations.